RHINO: reconfigurable hardware interface for computation and radio - Scott, Simon (Department of Electrical Engineering, 2015)
Field-programmable gate arrays, or FPGAs, provide an attractive computing platform for software-defined radio applications. Their reconfigurable nature allows many digital signal processing (DSP) algorithms to be highly parallelised within the FPGA fabric, while their customisable I/O interfaces allow simple interfacing to analogue-to-digital converters (ADCs) and digital-to-analogue converters (DACs). However, FPGA boards that deliver sufficient performance to be useful in real-world applications are generally expensive. Rhino is an FPGA-based hardware processing platform that primarily supports software-defined radio applications. The final cost estimate for a complete Rhino system is under $1700, cheaper than similar FPGA boards that deliver much lower performance.